â€œMixed-solvency approachâ€ â€“ Boon for solubilization of poorly water-soluble drugs - Maheshwari, R K (Asian Journal of Pharmaceutics (AJP), 2014)
Based on a large number of experiments on solubilization of poorly water-soluble drugs, the author is of the opinion that hydrotropy is another type of cosolvency and all water-soluble substances whether liquids, solids, or gases may act as solubilizers for poorly water-soluble drugs. In the present investigation, a mixed-solvency approach has been utilized for solubility enhancement of poorly water-soluble drug, salicylic acid (as a model drug). Sixteen blends (having total 40% w/v strength of solubilizers) containing various solubilizers among the commonly used hydrotropes (urea and sodium citrate), cosolvents (glycerin, propylene glycol, PEG 300 and PEG 400), and water-soluble solids (PEG 4000 and PEG 6000) were made to study the influence on solubility of salicylic acid. Twelve blends were found to increase the solubility of salicylic acid, synergistically. This approach shall prove a boon in pharmaceutical field to develop various formulations of poorly water-soluble drugs by combining various water-soluble excipients in safe concentrations to give a strong solution (say 25% w/v or so) to produce a desirable aqueous solubility of poorly water-soluble drugs. In the present investigation, the mixed-solvency approach has been employed to analyze salicylic acid in the bulk drug sample (using six blends) precluding the use of organic solvents (a way to green chemistry).